Realigning Agricultural Support to Promote Climate-Smart Agriculture - World Bank Group (World Bank, Washington, DC, 2018)
This note, prepared by the World Bank Food and Agriculture Global Practice ahead of the 24th Conference of the Parties to the United Nations Framework Convention on Climate Change examines the case for realigning agriculture support to promote climate-smart agriculture. From 2015 to 2017, the group of 51 countries analyzed provided approximately 570 billion US dollars annually in public support for agricultural producers, according to the Organisation for Economic Co-operation and Development (OECD). Distortionary agricultural subsidies often result in large negative impacts, worsening rather than improving climate outcomes. Significant opportunities exist to realign public support to deliver public-good outcomes and, in particular, promote climate-smart agriculture (CSA).